2007
DOI: 10.1186/1752-1947-1-153
|View full text |Cite
|
Sign up to set email alerts
|

Successful removal of a telephone cable, a foreign body through the urethra into the bladder: a case report

Abstract: The variety of foreign bodies inserted into or externally attached to the genitourinary tract defies imagination and includes all types of objects. The frequency of such cases renders these an important addition to the diseases of the genitourinary organs. The most common motive associated with the insertion of foreign bodies into the genitourinary tract is sexual or erotic in nature. In adults this is commonly caused by the insertion of objects used for masturbation and is frequently associated with mental he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 9 publications
0
65
0
8
Order By: Relevance
“…[7] In their series of 17 cases, Rahman et al [8] indicated psychiatric disorders, and auto-erotic drives as causes of self-insertion of foreign substances. In addition, Trehan et al [9] reported a patient without any psychiatric disorder, but experienced post-MI erectile dysfunction, and inserted telephone cables for erection, and sexual satisfaction. [9] Besides, Kılıç et al [10] reported a case of extraurethral self-insertion where a prisoner cut his penis to place a piece of mica inside his penis.…”
Section: Discussionmentioning
confidence: 99%
“…[7] In their series of 17 cases, Rahman et al [8] indicated psychiatric disorders, and auto-erotic drives as causes of self-insertion of foreign substances. In addition, Trehan et al [9] reported a patient without any psychiatric disorder, but experienced post-MI erectile dysfunction, and inserted telephone cables for erection, and sexual satisfaction. [9] Besides, Kılıç et al [10] reported a case of extraurethral self-insertion where a prisoner cut his penis to place a piece of mica inside his penis.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing the literature, most common motive of inserting a foreign object through the urethra is found to be autoerotism, sexual curiosity and gratification 4 . Male people had higher selfinsertion rates than females (1.7/1) 8 .…”
Section: Discussionmentioning
confidence: 99%
“…The patient may be completely asymptomatic or present with simple urethritis and cystitis symptoms such as pelvic pain, frequency, urgency, dysuria, strangury, microscopic or macroscopic, hematuria, purulent urethral discharge, fever or sometimes more serious like bladder perforation, ascending urinary tract infection and sepsis [2][3][4]6,7 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations